PELAKSANAAN PEMENUHAN KEWAJIBAN PAJAK PENGHASILAN PASAL 23 ATAS JASA LOUNDRY OLEH ISTANA KEPRESIDENAN BOGOR TAHUN 2014 - Ahmad Junaidi; Edy Edy; Fahmi Jazuli (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2015)
Article 23 Income Tax is a withholding tax on income received or obtained by domestic taxpayers and permanent business entities originating from service investment capital or conducting activities other than those already deducted by Article 21 Income Tax. The author will also discuss taxation in general, tax function and the tax collection system. The Legal Platform consists of Income Tax accompanied by Subject and Object of Income Tax, Income Tax Article 23 which is accompanied by the presence of the subject and is not subject to tax. The purpose of this study was to determine the general provisions of Article 23 Income Tax deduction by the Bogor Presidential Palace. One way to collect this final project data is by observation and interview. From the results of the study it can be concluded that the Bogor Presidential Palace has not carried out tax obligations in accordance with the applicable Law.